2010
DOI: 10.1089/aid.2010.0024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antioxidants on Mitochondrial Function in HIV-1–Related Lipoatrophy: A Pilot Study

Abstract: We investigated the effect of antioxidant supplementation on mitochondrial function, fat distribution, and lipid and glucose metabolism in HIV-1-infected patients with antiretroviral therapy (ART)-related lipoatrophy. 61 ART-treated HIV-1-infected patients with lipoatrophy were randomized to receive either n-acetyl-L-carnitine (n = 21), lipoic acid + n-acetylcisteine (LA/NAC) (n = 20), or no supplementation (n = 20) for 48 weeks. At baseline and at the end of treatment, mitochondrial function was studied by (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Some studies and clinical research found that some ART toxic effect could partially be reversed by previous and concomitant antioxidant treatment [74,75].…”
Section: Oxidative Stress During Antiretroviral Treatmentmentioning
confidence: 99%
“…Some studies and clinical research found that some ART toxic effect could partially be reversed by previous and concomitant antioxidant treatment [74,75].…”
Section: Oxidative Stress During Antiretroviral Treatmentmentioning
confidence: 99%
“…Mallon (2007), Miro et al (2005), Milazzo et al (2010) and Vassimont et al (2010) mentioned that the body shape abnormalities in HIV evolution include subcutaneous fat atrophy and visceral or central fat accumulation. The metabolic abnormalities include elevations in serum triglycerides and total cholesterol, suppression of serum high-density lipoprotein cholesterol levels, and hyperinsulinemia in normoglycemic individuals.…”
Section: Toxicity During Antiretroviral Treatment and Associated Disementioning
confidence: 99%
“…Meanwhile Masiá et al (2007) found increased plasma peroxide associated with established cardiovascular risk factors in the study context. McComsey et al (2005) describe some clinical and metabolic benefits during replacement of antiviral treatment while others by Milazzo et al (2010), Yousefi et al (2011), Hurwitz et al (2007 and Gil et al (2005a) found clinical and metabolic benefits during dietary micronutrient intake improvement in treatment or naive patients. For several years, the attention of different research groups as Aukrust et al (2003), Hulgan et al (2006) and Hurwitz et al (2007) has been largely focused on damages induced by ART on mtDNA and on the consequence of its depletion.…”
Section: Toxicity During Antiretroviral Treatment and Associated Disementioning
confidence: 99%
See 2 more Smart Citations